Risk factors for measles in children aged 8 months–14 years in China after nationwide measles campaign: A multi-site case-control study, 2012–2013. Issue 51 (12th December 2016) - Hao, Lixin; Ma, Chao; Wannemuehler, Kathleen A.; Su, Qiru; An, Zhijie; Cairns, Lisa; Quick, Linda; Rodewald, Lance; Liu, Yuanbao; He, Hanqing; Xu, Qing; Ma, Yating; et al.
Highlights: Vaccine efficacy of measles containing vaccine in China very high. Missed routine vaccination primary risk factor for measles infection in children. Lack of timely vaccination linked to recent migration and missed opportunities. Similar to infants, hospital exposure strongly associated with measles. Strengthened hospital infection control and vaccine outreach efforts required. Abstract: Introduction: Endemic measles persists in China, despite >95% reported coverage of two measles-containing vaccine doses and nationwide campaign that vaccinated more than 100 million children in 2010. In 2011, almost half of the 9943 measles cases in China occurred in children eligible for measles vaccination. We conducted a case-control study during 2012–2013 to identify risk factors for measles infection in children aged 8 months–14 years. Methods: Children with laboratory-confirmed measles were age- and neighborhood-matched with three controls. We interviewed parents of case and control infants on potential risk factors for measles. We calculated adjusted matched odds ratios and 95% confidence intervals of risk factors. We calculated attributable fractions for risk factors that could be interpreted as causal and vaccine efficacy (VE) for the measles containing vaccine (MCV) used in the Chinese immunization program. Results: In all, 969 case-patients and 2845 controls were enrolled. In multivariable analysis, lack of measles vaccination both overall (mOR 22.7 [16.6, 31.1] and when stratified by region (east region, mOR 74.2 [27.3, 202]; central/western regions mOR 17.4 [12.5, 24.3]), hospital exposure (mOR 63.0, 95% CI [32.8, 121]), and migration among counties (overall mOR 3.0 [2.3, 3.9]) were significant risk factors. The calculated VE was 91.9–96.1% for a single dose of MCV and 96.6–99.5% for 2 doses. Conclusions: Lack of vaccination was the leading risk factor for measles infection, especially in children born since the 2010 supplementary immunization activity. Reducing missed vaccination opportunities, improving immunization access for migrant children, and strengthening school/kindergarten vaccine checks are needed to strengthen the routine immunization program and maintain progress toward measles elimination in China.